Thermodynamics - Mohammad noor jalil; Siti Kartina Abdul Karim; Noor Hafizah Uyup (Penerbit Universiti Teknologi Mara, 2013)
This book is geared towards fulfilling the basic knowledge of thermodynamics for undergraduates as wll as those in other related fields. Written in easy to undertsnad and simple texts are realistic and informative introductions as well as numerous examples.